Prospects for China’s BRI and Strategic Influence in the Post-COVID-19 Central Asia - Khan, Furqan (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2021)
COVID-19 brings a momentous decline for global economic activities but its consequences for China’s Belt and Road Initiative (BRI) remains imminent. Despite the economic shocks of the Pandemic, BRI remains a top priority for China which allows Beijing to improve regional connectivity and expand its economic outreach far off to Europe and the American shores. On the other hand, the Central Asian economies are hard hit by the pandemic with a reduced regional trade, decline in oil prices and its commodities, deep slump in remittances, and the slackening manufacturing ability. The revival of BRI and its immediate success is desirable to the COVID-19 hit Central Asian economies. This is because BRI has bound the region together in terms of infrastructural development where China, under the rubric of BRI, is spearheading major developmental projects, pouring investment in energy sector, offering debt, and improving bilateral trade with regional economies. For this reason, the Central Asian countries desire immediate revival of close economic cooperation which could links the economic fortunes of regional countries to Beijing and brings the BRI to the fore in regional priorities. The paper highlight the impact of COVID-19 over Central Asian economies, the significance BRI for the region; its geopolitical importance for China; and the growing Chinese influence in the post-Pandemic Central Asia using Bourdieu’s Theory of Symbolic Power. Finally, using qualitative content analysis, the paper argues that the economic impact of COVID-19 are short-term and of limited nature and it will only increase prospects for BRI in the post-Pandemic Central Asia with vital strategic utilities for China’s geopolitical profile in the region.

COVID-19 przynosi doniosły spadek globalnego rozwoju gospodarczego, a jego konsekwencje dla chińskiej inicjatywy Belt and Road Initiative (BRI) pozostają także nieuchronne. Pomimo wstrząsów gospodarczych pandemii, BRI pozostaje głównym priorytetem dla Chin, co pozwala Pekinowi poprawić łączność regionalną i rozszerzyć zasięg gospodarczy na Europę i amerykańskie wybrzeża. Z drugiej strony, pandemia mocno dotknęła gospodarki Azji Środkowej, w związku z ograniczeniem handlu regionalnego, spadkiem cen ropy naftowej i jej towarów, głębokim spadkiem przepływów pieniężnych oraz słabnącą zdolnością produkcyjną. Ożywienie BRI i jego natychmiastowy sukces jest pożądany. Dzieje się tak, ponieważ BRI połączył region w zakresie rozwoju infrastruktury, gdzie Chiny, pod nazwą BRI, inicjują duże projekty rozwojowe, inwestując inwestycje w sektor energetyczny, oferując zadłużenie i poprawiając dwustronny handel z regionalnymi gospodarkami. Z tego powodu kraje Azji Środkowej pragną natychmiastowego ożywienia oraz bliskiej współpracy gospodarczej, która mogłaby powiązać losy gospodarcze krajów regionalnych z Pekinem i wysunąć BRI na pierwszy plan w priorytetach regionalnych. Artykuł podkreśla wpływ COVID-19 na gospodarki Azji Środkowej, znaczenie BRI dla regionu; jego geopolityczne znaczenie dla Chin; oraz rosnące wpływy chińskie w post-pandemicznej Azji Centralnej za pomocą teorii siły symbolicznej Bourdieu. Wreszcie, korzystając z jakościowej analizy treści, artykuł argumentuje, że wpływ gospodarczy COVID-19 jest krótkoterminowy oraz ograniczony, i tylko zwiększy perspektywy dla BRI w post-pandemicznej Azji Środkowej, z istotnymi strategicznymi narzędziami dla profilu geopolitycznego Chin w regionie.
Perspektywy chińskiego BRI w wpływy strategiczne w Azji Środkowej w epoce post-COVID-19
Keywords: BRI; China; Central Asia; COVID-19; Trade; Kyrgyzstan; Uzbekistan; geopolitical significance